OYO Rooms: Demystifying the Success of India’s New Age Hospitality Start-Up - Sardar, Ramesh (AMC Indian Journal of Entrepreneurship, 2019)
With the advent of app based technology enabled startups in India in various sectors like food, travel and hotels, competition has become rampant. This requires enterprises to be highly scalable and sustainable in the long run. Customers want quick response, quality, transparency, and ease of transactions. India’s new age hospitality startups are reciprocating in a very positive way to all these challenges. In fact, It is not about smartphone technology and apps but about breakthrough technological process used to create and deliver innovative products and experiences to the consumers. As per the Statista report, the Indian hotel market is expected to grow to around $13 billion by 2020 from $7 billion in 2015.This case study highlights how a young and innovative entrepreneur, Ritesh Agarwal started his venture OYO (On Your Own) rooms and fulfilled not only his dreams, but also the aspirations of millions of Indian families looking for budget hotels. OYO rooms was among the first to bridge the gap of customer expectations and perceptions, and initiated the process of branding the domestic budget hotel segment in the price range of 1000 to 3000. Today OYO is India’s largest network of branded hotels and has been successful in creating an innovative model in the hospitality sector. OYO has an estimated 1,25,000 exclusive rooms under its management and a presence in 230 cities. While Clear Trip, Make My Trip, and Goibibo are deep pocketed players in the online travel and tourism space, hotel chain OYO is one of the eight startups in India to enter the unicorn club in 2018. Undoubtedly, OYO Rooms has made significant use of technology to provide customers hassle-free standardized experience, but still there are numerous challenges in maintaining sustainability in the long run. The case highlights the growth story of new age startup OYO Rooms, its business model, and the challenges faced by OYO in expanding its business overseas.